The Relation between Body Mass Index and Hypotension Incidence in Caesarean Section Patients with Spinal Anesthesia Procedure - Valentia Josephine, Clara; Suparto, Suparto; Winata, Deadora (Malikussaleh University, Aceh, Indonesia, 2024)
One of the adverse consequences of spinal anesthesia is hypotension. Previous investigations regarding the correlation between post-spinal anesthetic hypotension and body mass index have yielded inconsistent results. This investigation predicted the Indonesian population using the body mass index computed according to the Asia-Pacific categorization. This investigation aimed to determine the correlation between body mass index and the frequency of hypotension following spinal anesthetic interventions for cesarean sections—quantitatively based on analytical observational research. 111 samples met the inclusion and exclusion criteria used in the study between May and August of 2022. An observation sheet is employed to obtain measurements of the patient's height, weight, and systolic blood pressure before and after spinal anesthesia. Type I obesity is associated with the greatest incidence of hypotension (25–30 kg/m2). Out of the 75 samples (67.6%) that were free of hypotension, 36 samples (32.4%) were affected by it. p-value of 0.322 for the Kruskal-Wallis test. In individuals who undergo spinal anesthetic treatments through cesarean sections, there is no significant correlation between body mass index and the frequency of hypotension. The results demonstrated that 36 samples (32.4%) experienced hypotension, while 75 samples (67.6%) did not. In individuals with a high body mass index and type I obesity (25–30 kg/m2), hypotension is most prevalent. There is no significant correlation between the frequency of hypotension following spinal anesthetic treatments and body mass index.